The Degree of Exercise of Academic and Sports Freedom among Faculty Members at the Colleges of Physical Education and Sports Sciences in Baghdad (American Journal of Physical Education and Health Science, 2024)
The faculties of physical education and sports sciences have made great contributions to the development of the Iraqi individual educationally, physically, and skillfully, so they were the developed academic resource for proper sports upbringing, and the author has tried to offer a practical and analytical framing of the views of the research sample regarding sports academic freedom, Being a civilized thought that establishes a promising organizational culture that preserves the country’s cultural heritage and develops the energies and resources to manage the present and the future, as well as enhancing the faculty’s confidence in the abilities and preparations for rapid adaptation to various variables in the labor market, the research has tried to answer the question that formed the research problem. The researcher has tested the correlation and influence between the axes of the sports academic freedom scale, which was built according to the scientific conditions for building educational and psychological standards, as well as measuring the degree of sports academic freedom practiced by the teaching staff at the colleges of physical education and Sports Sciences in Baghdad, the research has concluded several theoretical and practical conclusions, the most important of which: (1) The field research data revealed that there is a correlation and a moral impact between the axes of academic sports freedom in the colleges of physical education and Sports Sciences in Baghdad. (2) The field research data indicated that the colleges administration strengthened academic and sports freedom in the field of (teaching, freedom of expression and scientific research), without taking the field of decision-making, where it was the lowest degree compared to the rest of the axes.